Pengaruh Kemampuan Membaca Al-Qur’an dan Minat Belajar Siswa Terhadap Hasil Belajar Pelajaran Pendidikan Agama Islam (PAI) Pada Siswa Kelas X di SMA IT Iqra’ Kota Bengkulu - Marti Widiya; M Nasron (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to analyze the relationship between Qur'an reading ability and students' leammg interest towards the learning outcomes of Islamic Religious Education (PAI) at SMAIT Iqra' in Bengkulu City. Islamic Religious Education plays a vital role in shaping students' character and instilling Islamic values. Qur'an reading ability is considered a fundamental skill, especially for understanding and practicing the Qur'an's teachings in daily life. Leaming interest is also an essential factor influencing students' academic achievement in PAI subjects. This study employs an associative quantitative approach, with the population comprising tenth-grade students at SMAIT Iqra'. Data were collected through interviews, observations, and document analysis techniques. The research findings indicate a positive and significant relationship between Qur'an reading ability and PAI learning outcomes, with a significance value of 0.000 (<0.05). Furthermore, students' learning interest also demonstrates a positive relationship with learning outcomes, with a significance value of 0.002 (<0.05). Simultaneous regression analysis shows that both variables collectively contribute significantly to students' learning outcomes. This research provides practical implications for teachers and educational institutions to enhance Qur'an reading programs and. engaging learnin_g strategies to foster students learning interest. By improving Qur'an readmg skills and rnotrvatmg students m learnmg PAI· it is expected to cultivate a generation that excels academically and upholds high values of faith and morality.